The story so far : play therapy narratives - Cattanach, Ann (Jessica Kingsley Pub., 2002)
Identity is formed through the narration of experience, and children who experience difficult life events may need help in forming and expressing their own narratives. Play therapy can be a very appropriate way of facilitating this kind of expression. This book describes the work of nine play therapists through the narratives of children - and some adults - whose stories emerge during their play therapy sessions. These stories are not direct accounts of real happenings but are imaginative, metaphorical, complex and multi-layered. The life events they relate to include fostering, long-term illn.